The McGraw-Hill book of poetry - DiYanni, Robert (McGraw-Hill, 1993)
This is, perhaps, the widest ranging, most comprehensive poetry collection available, and it is useful for poetry courses at all levels. It contains an excellent introduction to reading poetry and understanding the elements, as well as sections on poems and paintings, poems and music, and poems from other languages. Sections on featured poets are integrated with the chronological anthology which gives students a perspective on the variety and range of a large group of poets. This multi-national, multi-cultural, multi-genre and multi-lingual collection gives students a view and instructors an opportunity to teach the universality of poetry. Includes a superb historical range of poetry, from its recorded beginnings to most contemporary.